Application of SERS in In‐Vitro Biomedical Detection. Issue 4 (13th January 2023) - Chen, Yunfan; An, Qi; Teng, Kaixuan; Liu, Chao; Sun, Fuwei; Li, Guangtao
Abstract: Surface‐enhanced Raman scattering (SERS), as a rapid and nondestructive biological detection method, holds great promise for clinical on spot and early diagnosis. In order to address the challenging demands of on spot detection of biomedical samples, a variety of strategies has been developed. These strategies include substrate structural and component engineering, data processing techniques, as well as combination with other analytical methods. This report summarizes the recent SERS developments for biomedical detection, and their promising applications in cancer detection, virus or bacterial infection detection, miscarriage spotting, neurological disease screening et al. The first part discusses the frequently used SERS substrate component and structures, the second part reports on the detection strategies for nucleic acids, proteins, bacteria, and virus, the third part summarizes their promising applications in clinical detection in a variety of illnesses, and the forth part reports on recent development of SERS in combination with other analytical techniques. The special merits, challenges, and perspectives are discussed in both introduction and conclusion sections. Abstract : Surface‐enhanced Raman scattering (SERS) promises hold great promise for clinical on spot and early diagnosis. In this review, we summarize the research progress of SERS in in‐vitro bioassays from the aspects of SERS substrate classification, detection principle and biological application.